On teaching the concepts of number sequence and its limit in academic lyceums - Aroyev Dilshod Davronovich; Yusupova Aigul Rustamjon qizi (Researchparks Publishing, 2023)
This article analyzes the teaching of the concepts of number sequence and its limits in academic lyceums and offers suggestions for its improvement.